Community mobilization around social dilemmas: evidence from lab experiments in rural Mali - Alzúa, María Laura (2014)
Community mobilization is a key feature of community-based development projects. Community mobilization requires facilitating communication between village members and between leaders and the rest of the community. Is communication an effective device through which mobilization may foster collective action? Does informing the community on how to reach a better social outcome key? Should we expect the effectiveness of community-based programs to depend on the quality of leadership in the community? In rural communities of Mali, we find evidence of high levels of cooperation as measured by a standard public good game. Communication between players increases contributions to the public good. Passing of information through a random community member also improves cooperation, and leadership skills matter. We also find suggestive evidence that changes in behavior are mediated through changes in beliefs. The experiments are embedded in a larger randomized controlled trial designed to evaluate the impact of a community-based sanitation intervention. As such, our results are relevant for a large population. Finally, we find that the program help strengthen the capacity for collective action.